PERANCANGAN STRUKTUR PENOPANG TANGKI PENYIMPANAN AMONIA - Anis Rosyidah; SUHAILI YARHAM (Jurnal Poli-Teknologi, 2014)
ABSTRACT This study to obtain reinforcement in the supporting structure of the ammonia storage tank which consisting of wall slab and top slab. Fisrt, done the modeling structure that will analyze and provide load acting on the structure. For modeling and loading on wall slab author use the program etabs v.9, while the top slab used for the safe program v.8. Special for top slab reinforcement analysis using the program. The results for top slab reinforcement consist of reinforcement x directions and y direction (see appendix 2), so that obtain the bottom reinforcement of x direction : d13 - 200, the bottom reinforcement of y direction : d13 - 200, the top reinforcement of direction x direction : d13 - 200, and the top reinforcement of y direction : d13 - 200. There are two types of wall slab, which is exterior wall and interior wall. Reinforcement in the walls consist of vertical and horizontal bars (see appendix 2), so that obtain the vertical exterior wall reinforcement: d13 - 200, horizontal exterior wall reinforcement: d13 - 400, vertical interior wall reinforcement: d13 - 350, horizontal interior wall reinforcement : d13 - 350. As a coupling between the wall slabs is used couple beam (spandrel), and results of spandrel reinforcement consist of main top reinforcement: 5 d13, the main bottom reinforcement : 5 d13, shear reinforcement : 2 d10 - 100, and shrinkage reinforcement : 2 d13. Keywords: reinforcement, top slab, wall slab, spandrel ABSTRAK Studi ini bertujuan untuk mendapatkan penulangan pada struktur pendukung tangki amonia yang terdiri dari wall slab dan top slab. Langkah awal dimulai dengan melakukan pemodelan struktur pada obyek yang ditinjau. Untuk pemodelan dan pembebanan wall digunakan program etabs v.9, sedangkan untuk top slab digunakan program safe v.8. Khusus untuk penulangan top slab dilakukan analisis dengan menggunakan program. Hasil penulangan top slab terdiri dari tulangan arah x dan arah y, dari hasil analisis diperoleh tulangan bawah arah x : d13 – 200, tulangan bawah arah y : d13 – 200, tulangan atas arah x : d13 – 200, dan tulangan atas arah y : d13 – 200. Pada wall slab terdapat 2 jenis dinding, yaitu dinding untuk bagian luar dan dinding pada bagian dalam. Untuk penulangan pada dinding terdiri dari tulangan vertikal dan horizontal, hasil yang diperoleh adalah tulangan vertikal dinding luar: d13 – 400, tulangan horizontal dinding luar: d13 – 400, tulangan vertikal dinding dalam: d13 – 350, tulangan horizontal dinding dalam: d13 – 350. Sebagai penghubung antar wall slab digunakan balok perangkai (spandrel), dan hasil penulangan untuk spandrel berupa tulangan utama atas : 5 d13, tulangan utama bawah : 5 d13, tulangan geser : 2 d10 – 100, tulangan susut : 2 d13. Kata kunci : penulangan, top slab, wall slab, spandrel.